PENGARUH PAPAN PETA BERPIKIR (MIND MAPPING BOARD) TERHADAP KEMAMPUAN MENGENAL BENTUK GEOMETRI PADA ANAK USIA 4-5 TAHUN DI TK PERTIWI KOTA PEKANBARU - Aisyah, Siti; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the effect of using a mind mapping board the ability to know the form geometry in children aged 4-5 years at kindergarten Pertiwi Pekanbaru city. The population in this research is grade B3 in kindergarten Pertiwi of as many as 21 children and the sample on this research as many as 21 children. The method used pre-experimental with the design one group pre test post design of experiments conducted in one group without the comparison group. This type of instrument used in this study is to use the observation and dokomentasi to take note of the activities of what’s happened in the treatment given, the equipment in use is the camera. Data was analyzed using statistical techniques t-test with SPSS for Windows Release 17.0. Based on the result of the hypothesis that there of the effect of mind mapping board of the ability to know the form geometry in children aged 4-5 years at kindergarten pertiwi pekanbaru city. Obtain value t count of 9,661 with significance 0.000. T table values obtained with df 19 at significance level of 5% (two-tailed) of 2.093. Thus known t count (9.661)> t table (2.093) or significance (0.000) <5% (0.05). It has been suggested that there is a difference in the results between the pretest and posttest significant. It is known that the result of higher than pretest posttest which can be seen from the descriptive statistical variable. The effect of mind mapping board of the ability to know the form geometry in children aged 4-5 years at kindergarten pertiwi Pekanbaru city as much as 26,25%..Key Words: The Ability To Know The Form Geometry, Mind Mapping Board.